PERAMALAN JUMLAH KLAIM DENGAN MEMBANDINGKAN METODE DOUBLE EXPONENTIAL SMOOTHING DARI BROWN DAN DOUBLE EXPONENTIAL SMOOTHING DARI HOLT - Desviona, Nayla; Asriyati, Trima; Rahayu, Ditayatul; Yudha, Bangkit Prima (Perwira Journal of Science & Engineering, 2021)
Time series model is that model uses to prediction the future with the past data, one of example of time series is exponential smoothing. Exponential smoothing is repair procedure where’s it done continuely at forecasting by new data. In this research Exponential Smoothing metode applied to forecasting amount of claim in Health BPJS at jambi with use the data since january 2018 until Juli 2021,the steps use to get output of research there are 4 steps,these are 1) Data Identification, 2) Modeling, 3) Forecasting, 4) Evaluation of Forecasting Result with MAE(Mean Absolute Error) and MSE (Mean Square Error). Brown’s model for PNS class 1: PNS class 2 : NON PNS class 1 : , NON PNS class 2 : . Holt’s model for PNS class 1: ,.PNS class 2 : NON PNS class 1 : and NON PNS class 2 : . Both of two metodes have similar good performance. but Holt’s metode has error value (MAE) more little then Brown’s metode. this thing is so important for looked considering its importance a forecasting for he best increase quality and contribution by Health BPJS at Jambi staff for future. Time series model is that model uses to prediction the future with the past data, one of example of time series is exponential smoothing. Exponential smoothing is repair procedure where’s it done continuely at forecasting by new data. In this research Exponential Smoothing metode applied to forecasting amount of claim in Health BPJS at jambi with use the data since january 2018 until Juli 2021,the steps use to get output of research there are 4 steps,these are 1) Data Identification, 2) Modeling, 3) Forecasting, 4) Evaluation of Forecasting Result with MAE(Mean Absolute Error) and MSE (Mean Square Error). Brown’s model for PNS class 1: PNS class 2 : NON PNS class 1 : , NON PNS class 2 : . Holt’s model for PNS class 1: ,.PNS class 2 : NON PNS class 1 : and NON PNS class 2 : . Both of two metodes have similar good performance. but Holt’s metode has error value (MAE) more little then Brown’s metode. this thing is so important for looked considering its importance a forecasting for he best increase quality and contribution by Health BPJS at Jambi staff for future.